Development of special flexibility in volleyball players - Rzhanov, A. A.; Lebedinsky, V. Yu.; Akhmatgatin, A. A.; Yani, A. V. (Theory and Practice of Physical Culture, 2023)
bjective of the study was to determine the means and methods for developing the special flexibility of volleyball players, methods for assessing it and influencing the effectiveness of the performance of a technical element: receiving the ball with two hands from below after a serve or an attacking blow from an opponent.